2015
DOI: 10.1111/ejn.13033
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of peripheral nerve regeneration and target reinnervation in animal models: a critical overview

Abstract: Peripheral nerve injuries usually lead to severe loss of motor, sensory and autonomic functions in the patients. Due to the complex requirements for adequate axonal regeneration, functional recovery is often poorly achieved. Experimental models are useful to investigate the mechanisms related to axonal regeneration and tissue reinnervation, and to test new therapeutic strategies to improve functional recovery. Therefore, objective and reliable evaluation methods should be applied for the assessment of regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 118 publications
3
135
0
1
Order By: Relevance
“…Hence, the increase of MF in the NGF groups would be in accordance with other studies that describe an important role of NGF on axonal sprouting (Diamond et al, 1987;Gloster et al, 1992;Ruiz et al, 2004). Thus, histological quantification of MFs may result in an overestimation of the number of regenerated neurons (Navarro 2015) and only the retrotracer study provides reliable information on the number of regenerating neurons. For these reasons, in our study the positive effects of the NTFs loaded MPs were indicated by the effective growth of axons that were able to capture the retrotracer placed distal to the nerve conduit.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, the increase of MF in the NGF groups would be in accordance with other studies that describe an important role of NGF on axonal sprouting (Diamond et al, 1987;Gloster et al, 1992;Ruiz et al, 2004). Thus, histological quantification of MFs may result in an overestimation of the number of regenerated neurons (Navarro 2015) and only the retrotracer study provides reliable information on the number of regenerating neurons. For these reasons, in our study the positive effects of the NTFs loaded MPs were indicated by the effective growth of axons that were able to capture the retrotracer placed distal to the nerve conduit.…”
Section: Discussionsupporting
confidence: 88%
“…These results indicate that overall functional recovery was impaired in the injured αBC −/− animals. Reduction in paw area, braking duration, and propulsion duration is suggestive of sensory and motor impairment (28). We, therefore, validated the DigiGait findings using classical motor (rotarod and walking track) and sensory (Hargreaves, Dynamic Plantar, and von Frey Hair) behavioral tests.…”
Section: Sensory and Motor Behaviors Are Impaired In αBcmentioning
confidence: 66%
“…To study novel approaches in peripheral nerve reconstruction and nerve graft tissue engineering, the sciatic nerve (SN) is easily accessible and its length provides the opportunity of addressing long gap repair (Tos et al., 2009) with a number of functional tests (Navarro, 2016). The SN model, however, is often inflicted by automutilation behavior and the development of hamstring contractions, eventually reducing the number of animals available for analysis and the significance of the results (Navarro, 2016; Weber, Proctor, Warner, & Verheyden, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The SN model, however, is often inflicted by automutilation behavior and the development of hamstring contractions, eventually reducing the number of animals available for analysis and the significance of the results (Navarro, 2016; Weber, Proctor, Warner, & Verheyden, 1993). …”
Section: Introductionmentioning
confidence: 99%